Women's Opportunities to Migrate at a Young Age: Taking Advantage of the Momentum of Demographic Bonus - Musrayani Usman; Hasbi Hasbi; Mario Mario; Ria Renita Abbas; Rahmat Muhammad (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Indonesia is currently in a demographic bonus until 2035. Where the productive age shows that the number of young people in the age range of 15-29 in 2022 reaches 24.3 percent and this is the basic capital in development. There are several countries that have successfully managed the demographic bonus and become developed countries such as Japan, South Korea, China and Singapore. Based on modernization theory that economic development will affect the value system of society that leads to gender equality. The Demographic Bonus is a golden opportunity for a nation if utilized properly. But the question is whether Indonesia is ready to seize the opportunity. The purpose of this paper is how to reveal facts, phenomena, variables. The research method uses a literature study with a descriptive-qualitative analysis method based on literature review. The results of the study are that there are several reasons that encourage someone to migrate with economic, family, education and work motives. Currently, Indonesia faces challenges in human development. The arrival of young migrants will lead to population growth and human resource development. The decision to migrate between men and women has different driving and pulling factors, women's participation to migrate where women's labor force participation is only 53.41 percent compared to men's 83.87 percent.